The wisdom of the wise : the presence and function of Scripture within 1 Cor. 1:18-3:23 - Williams, H. H. Drake. (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 2001)
Paul's Jewish background and his use of Scripture have been enduring interest within New Testament scholarship. This study contributes to this discussion by examing the presence and function of Scripture in I Cor. 1:18-3:23. The author examines the precence and function of Scripture in the form of six citations, two allusions, and seven echoes within I Cor. 1:19-3:23. From the examination of the function of these texts, this work concludes that Paul's use of Scripture agrees with its original context and stands in line with a majority of early Jewish tradition. Moreover, this study suggests that Pavi's use of Scripture also helps to chart a way through a difficult section of his writing.